2021
DOI: 10.3390/met11030464
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of rhBMP-2 Protein and Nanotextured Titanium Alloy Surface to Improve Osteogenic Implant Properties

Abstract: One of the major limitations during titanium (Ti) implant osseointegration is the poor cellular interactions at the biointerface. In the present study, the combined effect of recombinant human Bone Morphogenetic Protein-2 (rhBMP-2) and nanopatterned Ti6Al4V fabricated with Directed irradiation synthesis (DIS) is investigated in vitro. This environmentally-friendly plasma uses ions to create self-organized nanostructures on the surfaces. Nanocones (≈36.7 nm in DIS 80°) and thinner nanowalls (≈16.5 nm in DIS 60°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Other authors have used femtosecond laser [103,104] or directed irradiation synthesis (DIS) [105,106] techniques to obtain micro-and nano-textured surfaces of titanium implants to improve osseointegration by the replication of bone structures, increasing protein attachment and therefore cell adhesion.…”
Section: Laser Ablationmentioning
confidence: 99%
“…Other authors have used femtosecond laser [103,104] or directed irradiation synthesis (DIS) [105,106] techniques to obtain micro-and nano-textured surfaces of titanium implants to improve osseointegration by the replication of bone structures, increasing protein attachment and therefore cell adhesion.…”
Section: Laser Ablationmentioning
confidence: 99%
“…Nanofeatures that mimic the native ECM have promoted cell attachment, osteogenesis and vascularization. 20,30 In this context, ALP enzyme, an early bone differentiation marker expressed by osteoblastic cells 50,51 on these irradiated porous substrates was evaluated at 7 and 14 days. On day 7, ALP activity increases on porous Ar + irradiated samples and their non-irradiated counterparts compared to FD (Figure 11A).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is present in the maturation and the beginning of the mineralization stages of osteoblast differentiation. 50,51 To evaluate the final stage of mineralization by mature osteoblasts 51 we used Alizarin red to quantify calcium nodule production on the surfaces (Figures 11C and S3), which appears to be higher in Porous Ti Ar + DIS samples compared to FD samples. The optical images in Figure 11D indicated evidence of red deposits localized on the porous surfaces, compared to FD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that this improved adhesion may result from the interplay between integrins and BMP receptors [ 16 , 50 ]. Mesa-Restrepo et al [ 51 ] reported that the presence of BMP-2 on Ti discs plays an important role in cellular adhesion and spreading of C2C12 cells by increasing of filopodia number per cell and vinculin expression. It was shown that BMP-2 enhances the formation of focal adhesions and stress fibers in osteoblasts by increasing α5 and β1 integrin expression and also triggers cell migration [ 52 ].…”
Section: Resultsmentioning
confidence: 99%